2017
DOI: 10.30704/http-www-jivs-net.363189
|View full text |Cite
|
Sign up to set email alerts
|

The effects of furnished cages on the behaviour of laying hens in the post-stress adaptation period.

Abstract: The aim of the study is to investigate whether housing laying hens in furnished cages in post-stress adaptation period causes any changes in behaviors or not. Due to the affects of animal welfare on production performance, the relationship between behavioral changes and egg production has also been studied. In the present study, 22 weeks old, 32 laying hens were used. The hens were subjected to transport. The transport procedure, including loading and unloading took 8 hours. Just after the transportation, bird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Consistent with our findings, a study on laying hens found that transport can reduce comfortable behavior but increase aggressive behavior ( Matur et al, 2017 ). In addition, our results showed that the high-decibel sound environment group had reduced feather pecking, cage pecking, aggression, comfort, and sham sandbathing behaviors.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with our findings, a study on laying hens found that transport can reduce comfortable behavior but increase aggressive behavior ( Matur et al, 2017 ). In addition, our results showed that the high-decibel sound environment group had reduced feather pecking, cage pecking, aggression, comfort, and sham sandbathing behaviors.…”
Section: Resultssupporting
confidence: 91%
“…(2013) demonstrated that early-enriched environmental experience could effectively reduce fear and stress response of broilers to future environmental changes. Matur et al. (2017) found that comfort behavior of laying hens in furnished cages increased and agonistic behavior decreased, compared with laying hens raised in conventional cages after transportation, indicating that enrichment of the environment was conducive to recovery of laying hens after transport stress.…”
Section: Introductionmentioning
confidence: 95%